Drug survival is not significantly different between biologics in patients with psoriasis vulgaris: a single‐centre database analysis. (21st August 2014) - Menting, S.P.; Sitaram, A.S.; Bonnerjee‐van der Stok, H.M.; de Rie, M.A.; Hooft, L.; Spuls, Ph.I.
Summary: Background: Drug survival depends on several factors such as dosing, effectiveness, quality‐of‐life improvement and safety, and could be seen as an overall marker for treatment success. Such data for biologics in psoriasis treatment are sparse. Objectives: To determine differences in drug survival between different biologics for psoriasis. Methods: Drug survival, dosing, Psoriasis Area and Severity Index (PASI) and Skindex‐29 at weeks 12 and 52, and adverse events of patients with psoriasis treated with a biologic registered in the local database of the Academic Medical Center, Amsterdam, were analysed. Patients were divided into those naive or non‐naive for treatment episodes with biologics. Results: Drug survival did not differ significantly for naive treatment episodes between the biologics (etanercept 85% to 64%, adalimumab 77% to 77%, infliximab 75% to 75% for year 1–4), or for non‐naive treatment episodes (etanercept 86% to 42%, adalimumab 84% to 56%, infliximab 68% to 43% for year 1–4; ustekinumab 84% to 57% for year 1–3). The naive group showed better drug survival and PASI 75 response at week 12, although the difference was not significant. A similar improvement of mean ∆PASI and mean ∆Skindex‐29 was observed at weeks 12 and 52 for all biologics for both groups, although no significant difference was seen between groups. Treatment termination was due mainly to nonresponse for all biologics. Conclusions: There was no significant difference in drug survival, mean ∆PASI or Skindex‐29 response at weeks 12 or 52 between the biologics or between the naive and non‐naive groups. Treatment termination was due mostly to nonresponse. Sequential treatment with the available biologics can be effective. Abstract : What's already known about this topic? Drug survival data for biological treatment of psoriasis are sparse. The reported data vary. What does this study add? With this prospective cohort study, new drug survival data are presented. In our cohort, drug survival did not differ significantly between the biologics or between patients with naive and non‐naive treatment episodes.